Successful Long-Term Use of Itraconazole for the Treatment of Aspergillus Diskospondylitis in a Dog. (20th January 2013) - Van Wie, Emiko; Chen, Annie V.; Thomovsky, Stephanie A.; Tucker, Russell L.
Abstract : A 5-year-old spayed female German shepherd dog was admitted with a history of generalized stiffness. Neurologic examination revealed mild paraparesis with multifocal spinal pain. Spinal radiographs and magnetic resonance imaging revealed diskospondylitis at L6-7 and multiple sites throughout the thoracolumbar spine. Biopsy of the intervertebral disk at L6-7 revealed a positive culture for Aspergillus species, and the dog was placed on itraconazole indefinitely. Clinical signs were significantly improved after two weeks of itraconazole. The dog was reevaluated 8 years later for unrelated reasons. No spinal pain was detected. Spinal radiographs revealed a fused L6-7 disk space and collapsed and sclerotic disk spaces at multiple sites. Itraconazole was tolerated by the dog with normal yearly liver enzyme values. To our knowledge, this is the first reported case of successful long-term use of itraconazole for the treatment of Aspergillus diskospondylitis in a dog.